(untitled) (Journal of The Colloquium for Information Systems Security Education, 2020)
To enhance the capabilities of a cyber defense collaborative, a psychometric analysis team was embedded in a collaborative incident response team. Collaborative incident response community members included the State of Colorado, the Colorado National Guard, Regis University, private companies, and others. The collaborative training developed when National Guard leadership saw the Rocky Mountain Collegiate Cyber Defense Competition held at Regis, and planning began around the potential of collaborative training. The case presented shows the progressive efforts that allowed this to move from enhancing training exercises to being embedded during live cyber defense operations. Some outcomes of the psychometric evaluation are presented here as an embedded quantitative study within the framing case analysis. The case analysis is then used to formulate a generalized model designed to support opportunities for a range of interdisciplinary collaboration in support of technical endeavors with operations security requirements as exemplified by cyber defense. The resulting model provides a framework for expanding research to other disciplines.